Study of Power Requirements of the Combined Moldboard Plow at Different Forward Speeds - Sadiq Jabar Muhsin (University of Thi-Qar Journal of agricultural research, 2025)
The experiments were carried out in one of the agricultural fields of the College of Agriculture, University of Basrah, using a split-plot design with three replications to study the influences of single factors and their interactions on the performance of the developed moldboard plow. The parameters studied involved: moldboard type (M1: conventional moldboard, M2: finned moldboard), rigid harrow types (H0: moldboard plow without rigid harrow, H1: moldboard plow with one row of rigid harrow, H2: moldboard plow with two rigid harrows) and forward speed (S1: 1.5 km h-1, S2: 2.5 km h-1, S3: 3.5 km h-1). The results showed a significant effect of individual factors on the performance variables. The moldboard with fins (M2) led to an increase in draft force (%p<0.05) compared to the conventional moldboard (M1) by 8.36%. H2 increased the draft force, reaching 17.60 kN compared to H0 by 35.18%. Forward speed had a significant effect (%p<0.05), whereas draft force increased from 16.86 kN to 14.04 kN when forward speed from 1.5 to 3.5 km h-1. The interactions were also significant (%p<0.05). The interaction treatment (M2*H2*S3) recorded the highest draft force value of 19.86 kN, while the interaction treatment (M1*H0*S1) recorded the lowest value of 10.55 kN. Furthermore, the highest slip percentage was observed with (M2*H2*S3) reaching 19.53%, while the lowest was observed with (M1H0S1) at 8.2%. In terms of fuel consumption, the combination (M2*H2*S1) recorded the highest rate at 35.37 L ha-1, while the combination (M1*H0*S3) recorded the lowest fuel consumption rate at 16.60 L ha-1.